2019
DOI: 10.2131/fts.6.287
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine-induced liver injury using type 2 diabetes Spontaneously Diabetic Torii-<i>Lepr<sup>fa</sup></i> (SDT fatty) rats as a model for human type 2 diabetes

Abstract: The diabetic state is considered to be one of the risk factors of drug-induced liver injury (DILI) because of the lower levels of glutathione for detoxification by conjugation with drugs. Carbamazepine (CBZ)-induced hepatotoxicity in humans is rare and unpredictable with the present state of knowledge, but it is somehow related to disturbance of glutathione metabolism, although data in this regard are limited. In order to estimate the potential risk of DILI in patients with type 2 diabetes mellitus (T2DM), we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Our previous investigation revealed that the SDT fatty rats have lower levels of hepatic GSH and GSSG, and the characteristics of glucose metabolism, liver function and hepatic glutathione synthesis in the SDT fatty rats are like those in T2DM patients (Takahashi et al, 2019a). In addition, allyl alcohol and carbamazepine induced liver injury more prominently in the SDT fatty rats than in the SD rats (Takahashi et al, 2019a(Takahashi et al, , 2019b. From these, the potential for allyl alcohol and carbamazepine to induce liver injury was assessed to be higher in diabetic patients than in non-diabetics (Takahashi et al, 2019a(Takahashi et al, , 2019b.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Our previous investigation revealed that the SDT fatty rats have lower levels of hepatic GSH and GSSG, and the characteristics of glucose metabolism, liver function and hepatic glutathione synthesis in the SDT fatty rats are like those in T2DM patients (Takahashi et al, 2019a). In addition, allyl alcohol and carbamazepine induced liver injury more prominently in the SDT fatty rats than in the SD rats (Takahashi et al, 2019a(Takahashi et al, , 2019b. From these, the potential for allyl alcohol and carbamazepine to induce liver injury was assessed to be higher in diabetic patients than in non-diabetics (Takahashi et al, 2019a(Takahashi et al, , 2019b.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, allyl alcohol and carbamazepine induced liver injury more prominently in the SDT fatty rats than in the SD rats (Takahashi et al, 2019a(Takahashi et al, , 2019b. From these, the potential for allyl alcohol and carbamazepine to induce liver injury was assessed to be higher in diabetic patients than in non-diabetics (Takahashi et al, 2019a(Takahashi et al, , 2019b. In the present study, we investigated the potential of simvastatin to induce DILI using the SDT fatty rats to estimate the risk of DILI in diabetic patients because simvastatin is used in diabetic patients and shows a positive higher reaction in a GSH adduct assay in vitro (Sakatis et al, 2012) although major metabolic pathway for simvastatin in humans is considered to be oxidation by CYP3A.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations